(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Despite the fact that gestational diabetes mellitus (GDM) typically goes away after delivery, women who have already been diagnosed with the condition are at a higher risk of having long-term metabolic disorders like type-2 diabetes. Upon delivery, women with a history of GDM should be observed for at least during 6-12 weeks in order to assess their glycemic status. Aims: The aim of this study was to observe the persistence of glucose intolerance and associated risk factors of GDM mothers at 6-12 weeks post-partum. Methods: This cross-sectional study included 222 mothers from December 2011 to December 2018 who had a history of GDM based on 2013 World Health Organization criteria. Mothers who fulfilled the criteria for diabetes in pregnancy (DIP) were excluded from the analysis. They were recruited consecutively at 6-12 weeks post-partum from ‘GDM Clinic’ as applicable with the elapse of time. GDM mothers were assessed by 75-gm oral glucose tolerance test (OGTT) for the persistence of glucose intolerance. The risk factors associated with the persistence of glucose intolerance were also recorded. Results: Out of 222 GDM, 150 (67.6%) were found normal, while 72 (32.4%) were abnormal glucose tolerance (AGT) [impaired fasting glucose IFG: 16 (7.2%), IFG-IGT: 20 (9%), impaired glucose tolerance IGT: 24 (10.8%) and diabetes mellitus (DM): 12 (5.4%)] following American Diabetes Association (ADA) criteria. The age of the mother was significantly different from AGT to normal glucose tolerance. Conclusion: A good number of GDM mothers express AGT at 6-12 weeks post-partum, which suggests it is necessary to follow GDM mothers after child birth. J Assoc Clin Endocrinol Diabetol Bangladesh, January 2023;2(1): 2-7